PEMEROLEHAN KEMAMPUAN PRAGMATIK ANAK SD NEGERI 2 DAN SD PERSIT (KARTIKA II-3) PALEMBANG BERDASARKAN KELAS SOSIAL - Santi Oktarina (Balai Bahasa Sumatera Utara, 2019)
The purpose of this study was to describe the acquisition of pragmatic abilities of children SDN 2 and SD Persit (Kartika II-3) Palembang based on social class. In detail, the research aims to describe the speech act of children by intent. The data collection was done by using observation, recording, recording, and interviews. Data sourced from utterances produced by elementary school students and elementary Persit N. 2 (Kartika II-3) Palembang based on social class respectively. Determination of social classes conducted objectively. The method used in the data analysis is a method of sorting southwest frontier with pragmatic techniques. From the results of research and discussion can be summarized as follows. First, four types of speech acts based on the intent of speech in the utterances of the research subjects, namely assertive, directive, commissive, and expressive. Second, from the utterances classified based on the intent of speech speech acts are known to characterize verbal and nonverbal marking each social class. Thirdly, there are differences in the frequency of speech, language characteristic verbal and nonverbal used by study subjects according to social class.